2012
DOI: 10.1371/journal.pone.0031951
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Derived from Probiotic Lactobacillus reuteri Suppresses TNF via Modulation of PKA and ERK Signaling

Abstract: Beneficial microbes and probiotic species, such as Lactobacillus reuteri, produce biologically active compounds that can modulate host mucosal immunity. Previously, immunomodulatory factors secreted by L. reuteri ATCC PTA 6475 were unknown. A combined metabolomics and bacterial genetics strategy was utilized to identify small compound(s) produced by L. reuteri that were TNF-inhibitory. Hydrophilic interaction liquid chromatography-high performance liquid chromatography (HILIC-HPLC) separation isolated TNF-inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
346
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(354 citation statements)
references
References 75 publications
2
346
0
6
Order By: Relevance
“…Probiotic Lactobacillus-mediated interventions have been shown to downregulate TNF-a in the colon, enhance gut barrier activity, and reduce overall reductions in colitis-related pathology. [46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic Lactobacillus-mediated interventions have been shown to downregulate TNF-a in the colon, enhance gut barrier activity, and reduce overall reductions in colitis-related pathology. [46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…81 Lactobacillus reuteri, a commensal in the human gut, expresses histidine decarboxylase that converts histidine to histamine. Therefore, a change in the population of this gut microbe can potentially modulate the levels of circulating histidine and histamine, 82 which in turn can affect the concentration of CNS histamine. 83 In another example, rats that are given Bifidobacterium infantis for 14 days showed increased concentrations of the serotonin precursor tryptophan in plasma, an effect that may be mediated by the altered expression of indoleamine-2,3-dioxygenase, a key enzyme in the kynurenine pathway of tryptophan degradation.…”
Section: Effect Of Bacterial Metabolites On the Central Nervous Systemmentioning
confidence: 99%
“…The model probiotic organism L. reuteri ATCC PTA 6475 (L. reuteri 6475) also produces histamine (18). L. reuteri-derived histamine suppressed TNF production by TLR2-activated THP-1 cells via activation of the histamine receptor type 2 (H 2 ) and inhibition of MEK/extracellular signal-regulated kinase mitogen-activated protein (MAP) kinase signaling.…”
mentioning
confidence: 99%